Dengue knowledge, practices, and Aaedes Larval populations in selected low and high dengue priority areas in Miag-ao, Iloilo - VML/ess 3.20.17; T-UG 1798
This cross-sectional study aimed to compare the knowledge, practices, and Aedes larval populations between low and high dengue priority areas of Miag-ao, Iloilo. Larval surveys were done to determine aedes larval populations, expressed as House Index (HI), Container Index (CI), and Breteau Index (BI).